2011
DOI: 10.1523/jneurosci.4240-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Allocation of Vision under Competing Task Demands

Abstract: Human behavior in natural tasks consists of an intricately coordinated dance of cognitive, perceptual, and motor activities. While much research has progressed in understanding the nature of cognitive, perceptual, or motor processing in isolation or in highly constrained settings, few studies have sought to examine how these systems are coordinated in the context of executing complex behavior. Previous research has suggested that in the course of visually-guided reaching movements, the eye and hand are yoked, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
4
13
0
Order By: Relevance
“…The behavioral results described by Miller are thus consistent with the view that the precision in the neural coding of information at the sensory and perceptual levels might contribute to the variations in our abilities to make absolute judgements across different dimensions of stimuli in different sensory modalities. This view is consistent with the ideal observer model of visual working memory proposed by Sims and colleagues (Sims, Jacobs, & Knill, 2011, which considers the distortion (the difference in precision between input and output signals) and the quantity of information that can be processed by a memory system to be fundamental determinants of memory performance.…”
Section: Absolute Judgementssupporting
confidence: 86%
“…The behavioral results described by Miller are thus consistent with the view that the precision in the neural coding of information at the sensory and perceptual levels might contribute to the variations in our abilities to make absolute judgements across different dimensions of stimuli in different sensory modalities. This view is consistent with the ideal observer model of visual working memory proposed by Sims and colleagues (Sims, Jacobs, & Knill, 2011, which considers the distortion (the difference in precision between input and output signals) and the quantity of information that can be processed by a memory system to be fundamental determinants of memory performance.…”
Section: Absolute Judgementssupporting
confidence: 86%
“…Although many factors may contribute to this variability in action outcomes, humans have been shown to take this variability into account (30). Further evidence for this comes from experiments that have shown that in a reproduction task the impact of prior knowledge on behavior increased according to the uncertainty in time estimation (31) and studies that extended an ideal observer to an ideal actor by including behavioral timing variability (32). To describe the variability of fixation durations we used an exponential Gaussian distribution (33) because it is a common choice for describing fixation durations (34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…In both studies, human performance was optimal in the sense that subjects chose the initiation time that maximized the probability of hitting the target. Humans also trade off the amount of time fixating the object of a reach and the goal where that object will next be placed based on the acuity requirements of each sub-task [14]. …”
Section: The Cost Of Timementioning
confidence: 99%